The Effect of GDP, Fertility Rate, and Female Education on Female Labor Force Participation Rate (LFPR) in ASEAN - Mahbuba, Laila Ayu; Setyowati, Eni (Universitas Muhammadiyah Surakarta, 2023)
Purpose: This research, employing a quantitative methodology, seeks to enhance the understanding of the Female Labor Force Participation Rate (LFPR) in ASEAN countries. By analyzing statistical data over an extended period beyond 2018-2021, the study aims to uncover the nuanced relationships between female LFPR as a dependent variable and GDP, fertility rate, and female education as independent variables. Research Methods: This study applies quantitative research methods and utilizes secondary data published by the World Bank. The data that has been collected is then analysed using panel data and CEM, FEM, and REM regression techniques. Results: GDP exhibits a significant and positive correlation. Meanwhile, fertility rate and female education also have a significant but each has a negative correlation with Female LFPR. Aplication/Originality/Value: This study analyses economic issues in developing countries in ASEAN, to better understand the dynamics of female LFPR and can become the basis for policies to empower the female labor force in the sector of the region under study. These concise implications provide a strategic roadmap for policymakers and organizations striving to empower women and drive sustainable economic development in the region.